2022
DOI: 10.3389/fmed.2021.744907
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic APACHE II Score to Predict the Outcome of Intensive Care Unit Patients

Abstract: ObjectiveThis study aims to evaluate the accuracy of the Acute Physiology and Chronic Health Evaluation (APACHE) II score on different days in predicting the mortality of critically ill patients to identify the best time point for the APACHE II score.MethodsThe demographic and clinical data are retrieved from the Medical Information Mart for Intensive Care (MIMIC)-IV dataset. APACHE II scores on days 1, 2, 3, 5, 7, 14, and 28 of hospitalization are calculated, and their performance is evaluated using the area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…Lee et al [ 2 ] used patients who had undergone living donor or deceased donor liver transplantation were admitted to the surgical ICU as the study population and obtained similar results. Besides, Tian et al [ 15 ] showed that the APACHE II score on day 3 of hospitalization was the best biomarker to predict prognosis in ICU patients. However, our results differ from the conclusions of existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 2 ] used patients who had undergone living donor or deceased donor liver transplantation were admitted to the surgical ICU as the study population and obtained similar results. Besides, Tian et al [ 15 ] showed that the APACHE II score on day 3 of hospitalization was the best biomarker to predict prognosis in ICU patients. However, our results differ from the conclusions of existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, out of 213 patients, only 41 were admitted to the ICU in our study. 24 This may be the reason why the AUC was low for this measure.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as the scoring system was initially created to predict the operative risk of adverse outcomes rather than short-term complications. 24 An intrinsic limitation of the ASA score is that it is a subjective tool. Grading may differ between anesthesiologists due to the subjective nature of the score.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of at least two of the findings was accepted as SIRS, and the presence of documented or suspected infection in this picture was accepted as sepsis. One of the scoring systems, the APACHE II (Acute Physiology and Chronic Health Evolution II) score, was used to evaluate the severity of the disease and predict the outcomes [18].…”
Section: Methodsmentioning
confidence: 99%